Experimental investigations of the structural transformations induced by the heat treatment in manganese ferrite synthesized by ultrasonic assisted co-precipitation method. Issue 15 (15th November 2016) - Malaescu, I.; Lungu, A.; Marin, C.N.; Vlazan, P.; Sfirloaga, P.; Turi, G.M.
Abstract: Manganese ferrite powder has been synthesized by ultrasonically assisted co-precipitation method using Fe(NO3 )3 ·2H2 O and Mn(NO3 )2 ·H2 O as precursors. The precipitate was washed and dried in oven at 80 °C for 2 h to obtain the initial MnFe2 O4 powder (denoted by sample S1). Subsequently, other three samples (denoted by S2, S3 and S4) were prepared starting from the initial powder, which was subjected to heat treatment (for 2 h in air) at 400 °C (for sample S2), 700 °C (for sample S3) and 1000 °C (for sample S4). The structural and morphological analysis of samples has been studied by X-ray diffraction (XRD) and scanning electron microscopy (SEM). From the XRD analysis of samples one finds that the samples S1 and S2 consist of MnFe2 O4 with cubic spinel structure, whilst the samples S3 and S4 consist of FeMnO3 with perovskite structure and Fe2 O3 ; meaning that the thermal treatment of MnFe2 O4 induces chemical and structural transformation. The complex impedance measurements, over the frequency range 20 Hz–2 MHz and magnetic measurements have confirmed the structural transformation in the samples subjected of heat treatment.